RDAVIDWebService: a versatile R interface to DAVID - Fresno Rodríguez, Cristóbal (2013)
The RDAVIDWebService package provides a class-based interface from R programs/scripts to fully access/control the database for annotation, visualization and integrated discovery, without the need for human interaction on its Web site (http://david.abcc.ncifcrf.gov). The library enhances the database for annotation, visualization and integrated discovery capabilities for Gene Ontology analysis by means of GOstats-based direct acyclic graph conversion methods, in addition to the usual many-genes-to-many-terms visualization.